IOT-BASED AIR QUALITY MONITORING SYSTEM IN THE SERVICES BUILDING OF THE INTEGRATED POLYTECHNIC UNIT BALIKPAPAN - Muhammad Taufik; Hilmansyah, Hilmansyah; Aditya, Angga Wahyu (JIMREK : Jurnal Ilmiah Rekayasa Elektro, 2025)
Making this final project aims to realize the design of the tool and determine the performance of the Internet of Things (IoT)-Based Indoor Air Quality Monitoring System and can be monitored via Blynk, and also using an ESP32 microcontroller assisted by the mq-7 sensor, GP2Y1010AU0F sensor, and mq-135 sensors. This tool works to measure indoor air quality. Based on the tests that have been carried out, it can be seen that the overall performance of the Internet of Things (IoT)-Based Indoor Air Quality Monitoring System has worked as expected, namely when the sensor detects air quality, the results are processed by the ESP32 microcontroller so that it can be displayed on the LCD. After testing the tool from 07.00 to 18.00, the measurement results are obtained, namely the MQ 7 sensor when detecting CO gas of 228.47 ppm, the MQ 135 sensor when detecting CO2 gas has an average of 1, 12 ppm and the GP2Y1010AU0F sensor has an average of 1.50 kg/nm3 when it detects dust particles.